A study on the environmental disclosure among Malaysian companies that are listed in KLSE under consumer products sector and finance sector / Asdila Mustafah - Mustafah, Asdila (Faculty of Business and Management, 2011)
This study focuses on the Environmental Disclosure among Malaysian companies that are listed in Kuala Lumpur stock Exchange (KLSE) main board. The main objective of the study is to examine the environmental disclosure among Malaysian companies that are listed in KLSE. Data are collected by using the annual reports of the companies for the year 2010. Companies from two (2) sectors has been chosen in order to do this research. There are consumer products sector and finance sector. The researcher study all the companies for two sectors that are listed in KLSE. There are 148 companies under consumer products sector and 37 companies from finance sector. The data will be keyed in into SPSS in order to see the frequency and to create the graph and chart.